Problems in management of tourism offer of Serbia - Cvetkovski, Tatjana; Langović Milićević, Ana; Cvetkovska Оcokoljić Violeta (Hotel and Tourism Management, 2014)
While many in the tourism industry see the key of the world economic development seems that in Serbia, tourism has not given enough attention.It is somewhat justified if we considermany problems that are directed to Serbia’s tourist offer. Unrecognizability of Serbia as a tourist destination in the international tourism market, the lack of qualified human resources in tourism professions and facilities, limited access to interesting destinations in Serbia, poor infrastructure are just some of the problems that Serbia faces.The aim of this paper is to highlight the problems in the field of tourism and in the defining of tourist offers in Serbia.